The discourse of Belarusian IT-companies on the Internet - Choumanskaya, Olga A. (Journal of the Belarusian State University. Philology, 2020)
The article describes the results of discourse analysis of corporate media texts of Belarusian IT-companies. Attention is paid to the socio-economic features of the functioning of the IT-sector in Belarus, target audiences, the main channels and formats of communication of Belarusian IT-companies. These formats include corporate websites and blogs, official pages on social networks Twitter and Facebook. The article discusses the communication functions and target audiences of each format. The genres of communication formats are presented, which include press releases, case stories, congratulations, news notes, analytical articles, interviews, business offers, vacancies, congratulations, wishes, announcements, appeals, information notes, long-reads. The article also describes the linguistic features of each communicative format. At the end of the article, conclusions are drawn on how the communication format, genre and target audience influence the language characteristics of the texts: the choice of language (Russian or English) and discursive means that determine the formal or informal nature of communication.